Program Kokoh Cerdas Sebagai Upaya Pencegahan dan Penanganan Stunting di Dusun Loncatan Desa Mangaran Kecamatan Ajung Kabupaten Jember: Program Kokoh Cerdas Sebagai Upaya Pencegahan Dan Penanganan Stunting - Utami, Bayu Tri; Wati, Lovia Fradella; Prasetyo, Eko; Anggariesta, Zhenvio Gilang; Romadhan, Khoirul; Susanto, Tantut (Jurnal Pengabdian Masyarakat dan Penerapan Ilmu Pengetahuan, 2025)
Problem solving in the stunting innovation program must be carried out through collaboration involving various parties, both internal and external parties. The innovation program is KOKOH DAN CERDAS (KOmpak & Harmonious Community in Handling & Preventing Stunting Risks) with the aim of reducing and preventing stunting incidents by involving cross-sectors where the planned program contains evidence-based programs so that program optimization can be measured, evaluated in a structured manner and the program can be developed into a sustainable program. This program is carried out for three months from November-December 2024. The method used in this activity is a method with a socialization and education approach accompanied by a pre-test and post-test. Pre-tests and post-tests are carried out to see the knowledge and attitudes of the target groups before and after intervention or education. This method uses a survey design to see changes in behavior in targets involved in preventing and handling stunting. The results of the community service showed that the level of knowledge, attitudes, and behavior of mothers about stunting was partly sufficient (50%), lacking (50%), and sufficient (37.5%). Meanwhile, the measurement of Food Recall using a food model photo instrument found that there were still many inconsistencies in the composition of food given to toddlers with stunting, and based on interviews with respondent mothers, it was found that they had been taught about food composition but only briefly at the integrated health post. A program and ongoing evaluation are needed to reduce stunting.